Strategic business sustainability: study of critical success factors - Silveira, Lauana Lobo; De Benedicto, Samuel Carvalho; Silva, Luiz Henrique Vieira da; Bittencourt, Josias Jacintho (Revista de Administração da UFSM, 2022)
Objective: This study aims to identify which are the Critical Success Factors (CSF) that permeate management practices and determine business sustainability, contributing to the achievement of the Sustainable Development Goals (SDGs). Methodology: The research has as characteristics: qualitative approach, exploratory objective and descriptive and explanatory design. The sampling of the research was intentional and involved bibliographic and documentary analysis. Results: The 51 selected documents indicate that there is a predilection for the environmental and economic dimensions, even though the social pillar is gaining ground as a strategic factor of sustainability. Final considerations: When comparing the results with the SDGs, it was found that fundamental topics for the maintenance of living conditions on Earth and for human prosperity were not contemplated in the Critical Success Factors in Sustainability (CSFS) with high repetition index. It is advocated that the SDGs are important paths for the implementation of sustainable actions in companies and, therefore, as CSFS.